2022
DOI: 10.1002/acr.24631
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performances of Ultrasound Evaluation of Major Salivary Glands According to the 2019 Outcome Measures in Rheumatology Ultrasound Scoring System

Abstract: Objective. To evaluate the diagnostic performance of ultrasound examination of the major salivary glands (US-SG) according to the 2019 OMERACT US scoring system for Sjogren's syndrome (SS).Methods. This was a retrospective study based on a multicentric cohort of SS/sicca syndrome. ACR/EULAR 2016 (≥ 4 without OSS), AECG 2002 and clinician experts were considered as reference standards for SSdiagnosis. An OMERACT score ≥ 2 according to 2 independent readers defined the diagnosis of SS based on US-SG assessment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Owing to the lack of imaging methods to visualize the major salivary glands, many researchers are interested in incorporating SGUS into the current ACR/EULAR criteria ( 4 , 22 , 24 ). A recent study demonstrated that the combination of positive SGUS and the presence of anti-SSA/Ro antibodies highly predicted the pSS classification according to the ACR/EULAR classification criteria ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to the lack of imaging methods to visualize the major salivary glands, many researchers are interested in incorporating SGUS into the current ACR/EULAR criteria ( 4 , 22 , 24 ). A recent study demonstrated that the combination of positive SGUS and the presence of anti-SSA/Ro antibodies highly predicted the pSS classification according to the ACR/EULAR classification criteria ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…In case of disagreement between the rheumatologists, the results obtained by the more experienced rheumatologist were used to analyse the diagnostic performance. A score ≥ 2 for the most affected salivary gland defined SGUS as compatible with a pSS diagnosis ( 4 ). A total of 0–12 total SGUS scores were calculated as the sum of the four glands.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 SGUS is economical and has become the most widely recognized auxiliary diagnostic tool. [6][7][8] However, it provides low-resolution images, and there are systematic training and high technical requirements for operators. In reality, there is a shortage of such specialists in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of imaging techniques, such as salivary gland ultrasound (SGUS), magnetic resonance imaging (MRI), magnetic resonance parotid sialography (MRS), X‐ray contrast, are increasingly used to diagnose and monitor the progression of pSS 4,5 . SGUS is economical and has become the most widely recognized auxiliary diagnostic tool 6–8 . However, it provides low‐resolution images, and there are systematic training and high technical requirements for operators.…”
Section: Introductionmentioning
confidence: 99%